HIV Treatment and Prevention Technologies in International Perspective
X, 210 p.
Keywords: This edited collection investigates the biomedical and social technologies used to control the HIV pandemic through case studies and critical commentaries from Africa, Europe, North America and Australia. With reference to global and local complexities, the volume engages with HIV treatment access, community-based health promotion, sexual health, HIV prevention and the relations between treatment and prevention. The volume includes chapters from leading authors in their fields and takes a trans-disciplinary approach by making reference to theoretical and empirical research from sociology, psychology, cultural studies and science and technology studies, thus helping to establish new ways of understanding current and future configurations of HIV technologies.